Perlaksanaan CSCW dalam QCC menggunakan metodologi ethics: kajian kes kumpulan APQ, Pejabat Harta Bina - Mansor, Maisarah Wahieda (2006)
Computer Supported Cooperative Work (CSCW) is a multi-disciplinary research field that focuses on tools and techniques to support a group of working people on related task. CSCW provides support to those individuals and organization to cooperate in group. Quality Control Circle (QCC) is part and parcel of the Total Quality Management (TQM) activity which contributes to the enhancement and progress of an organization. Moreover, QCC aids the organizations in quality control management. The focal point of this thesis is to the implementation of CSCW in QCC for raising the collaboration between the members to work in group as well as to improve the quality and productivity of the organization via web-based groupware system known as QCCtool system. The system will maintain the interaction of grouping by using groupware such as e-brainstorming, work-flow system, file sharing, e-mail, text message, bulletin board and group-calendar. QCCtool system was developed through the methodology of Effective Technical and Human Implementation of Computer-based Systems (ETHICS) as a requisite to the system development. The methodology was selected due to its capacity in fulfilling the vital two criteria which sustain the CSCW and QCC research namely social factor and organization. QCCtool system will serve each of the QCC members to collaborate with more effective and efficient in line with the QCC concept which stress on the spirit of cooperation among the group members.